Effects of Ruesie-Datton Exercise on Flexibility of Lower Lumbar in Female University Students - Pimdee, Atipong; Srichupruang, Chonnakarn; Yuttawarakul, Natsika; Phochai, Parinya (Health Science Journal of Thailand, 2025)
This experimental research aimed to compare the effects of Ruesie-Datton exercises on the flexibility of the lower back in female university students. A total of 58 volunteers were divided into two groups: the control group, consisting of 29 participants (aged 20.7 ± 0.9 years, BMI range of 20.6 ± 1.0 kg/m²), who received pamphlets providing information on exercises to improve lower back flexibility, and the experimental group, consisting of 29 participants (aged 18.6 ± 0.8 years, BMI range of 20.5 ± 1.8 kg/m²), who participated in a Ruesie-Datton exercise program, comprising six postures, performed for 40 minutes, three times per week for a duration of four weeks. Both groups were assessed for lower back flexibility using the Sit and Reach test and the modified Schober’s test, both before and after the experiment. The data obtained was analyzed using the Independent t-test statistic with IBM SPSS version 28.0. The study found that the control and experimental groups had Sit and Reach test values of -7.8 ± 1.85 and -0.85 ± 2.86 cm, respectively, and modified Schober’s test values of 3.66 ± 0.97 and 5.75 ± 0.97 cm, respectively. When comparing between the groups, a statistically significant difference was found (p < 0.001). Thus, it can be concluded that the Ruesie-Datton exercise program effectively increases lower back flexibility.